Measuring Customer Discrimination: Evidence from the Professional Cricket League in India - Pramod Kumar Sur; Masaru Sasaki (Institute of Labor Economics (IZA), 2018)
Research in the field of customer discrimination has received relatively little attention even if the theory of discrimination suggests that customer discrimination may exist in the long run whereas employer and employee discrimination may not. This paper examines customer discrimination considering a unique dataset from the most popular sports industry in India, i.e., cricket. Relying on Playing XI vote in the Indian Premier League (IPL), we analyze whether supporters have a different personal preference towards players based on their location of origin and religion. In contrast to the often-heated rhetoric surrounding discrimination, the often-unfounded assertions surrounding diversity, and the previous literature, we overall do not find any discrimination in voting. Our overall findings suggest that supporters treat players equally irrespective of nationality, place of origin or religious background while selecting their favorite players. However, our results also suggest that examining discrimination by controlling for proxy productivity characteristics may produce bias results as certain included or excluded characteristics may be systematically different. Our findings further suggest that political conflict may lead to customer discrimination. And finally, in line with Heckman's (1998) argument, our results suggest that customer discrimination may exist on the margin.
Keywords: Z22; J71; L83; 330; customer discrimination; professional sports; cricket; India